Acid liquor thickening agent as well as preparation method and application thereof

By adopting the quaternary polymer structure of acid liquid thickening agent, the problem of poor stability of fracturing liquid thickening agent in the prior art is solved, and high viscosity, shear resistance, salt resistance and hardness resistance are achieved. The effect significantly improves the effect of acidification and fracturing operations.

CN119285832AActive Publication Date: 2025-01-10DONGYING ZHONGYUE PETROLEUM TECH CO LTD

Patent Information

Application Number
CN202411803399.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-01-10
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing fracturing liquid thickening agents break cross-link bonds at high temperatures, resulting in poor stability, viscosity less than 40mPa·s, and poor shear resistance, which cannot meet the needs of acidification fracturing operations.

Method used

Using an acid liquid thickening agent, its molecular structure includes butene glycol, 4,4'-diaminodisyl-2,2'-disulfonic acid, (2-acrylaminoethyl)phosphonic acid and (3-acryloyloxypropyl)tris(trimethylsiloxy)silane forms a quaternary polymer through a specific synthetic method, with high apparent viscosity, shear resistance and salt and hardness resistance.

Benefits of technology

It has achieved high apparent viscosity (124mPa·s and above), shear resistance (viscosity retention rate is greater than 88%), salt resistance and hardness resistance (apparent viscosity remains 100mPa·s and above at high temperatures), and has significantly improved Stability and drag reduction effect of fracturing fluid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of oil exploitation, and particularly relates to an acid liquor thickening agent as well as a preparation method and application thereof. The synthesis method comprises the following steps: adding butylene glycol, 4, 4 '-diaminostilbene-2, 2'-disulfonic acid, (2-acrylamido ethyl) phosphonic acid, monopotassium phosphate and deionized water into a first reactor, uniformly stirring, and adjusting the pH value to 7-8; (3-acryloyloxypropyl) tri (trimethylsiloxy) silane, deionized water, hydroxypropyl methyl cellulose, OP-10 and monopotassium phosphate are sequentially added into a second reactor, and the pH is adjusted to be 7-8; adding an initiator into a high-position dropwise adding tank, dropwise adding the initiator into a second reactor, quickly adding the mixed liquid in the first reactor when the viscosity begins to rise, heating, and carrying out heat preservation reaction to obtain viscous liquid; and drying and granulating to obtain the product. The invention has the advantages of simple synthesis, high apparent viscosity, strong shear resistance, good salt-resistant and hardness-resistant effects, and good drag reduction effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of petroleum extraction, and in particular relates to an acid liquid thickener and a preparation method and application thereof. Background Art

[0002] The purpose of fracturing is to create cracks in the reservoir, maximize the reservoir conductivity, and increase oil and gas production. The fracturing fluid used in fracturing is required to have high viscosity, high shear resistance, excellent sand carrying capacity, no residue after gel breaking, little damage to the formation, and environmental protection.

[0003] As the main agent of fracturing fluid, thickener is used to increase the viscosity of fracturing fluid, reduce fracturing fluid loss, suspend and carry proppant.

[0004] At present, the thickeners for fracturing fluid are mainly natural polymers such as guar gum, hydroxypropyl guar gum, carboxymethyl guar gum, and fennel gum. The properties and output of such thickeners are greatly affected by the environment and the place of origin. Another type of synthetic thickener is mainly polyacrylamide and its modified products, which have relatively stable performance, but have the disadvantage of poor shear resistance.

[0005] CN101864031A discloses a method for preparing a temperature-controlled variable-viscosity acid gelling agent by aqueous solution polymerization, comprising neutralizing 2-acrylamide-2-methylpropane sulfonic acid with a strong alkaline solution to a neutral pH, and sequentially adding acrylamide monomer and other olefin monomers in proportion. Azo initiators and oxidation / reduction initiators are added, and when the temperature of the polymerization system reaches the temperature peak, the system is kept warm and matured. The colloidal product is granulated, dried and crushed to obtain a temperature-controlled variable-viscosity acid gelling agent powder, and its hydrochloric acid solution uses formaldehyde / zirconium acetylacetonate as a cross-linking agent to perform a cross-linking reaction. The main components of the obtained gelling agent are amphoteric copolymers of acrylamide, 2-acrylamide-2-methylpropane sulfonate and methacryloyloxyethyl R-dimethylammonium chloride (R is an alkyl group of C1-C32). However, the viscosity of the gelling agent of the invention is less than 40mPa•s, and the effect of acid fracturing operation is obviously poor.

[0006] CN111019042A discloses a high temperature resistant thickener for fracturing fluid and its preparation method and application, including a high temperature resistant thickener for fracturing fluid, characterized in that the thickener includes acrylamide, salt resistant functional monomer and thermosensitive functional monomer free radical; the molar ratio of acrylamide, salt resistant functional monomer and thermosensitive functional monomer is 1: (0.01-0.08): (0.05-0.15). The invention introduces thermosensitive units and salt resistant units into the acrylamide molecular chain by solution copolymerization, giving the copolymer excellent high temperature resistance and salt resistance while having good solubility, viscoelasticity and sand carrying capacity. However, the invention does not actually solve the problem of cross-linking bond breakage of the fracturing fluid thickener at high temperature, resulting in poor stability of the fracturing fluid thickener. Summary of the invention

[0007] The present invention aims at the deficiencies of the above-mentioned prior art and provides an acid liquid thickener and a preparation method and application thereof. The present invention has the advantages of simple synthesis, high apparent viscosity, strong shear resistance, good salt resistance and hardness resistance, and good drag reduction effect.

[0008] The first object of the present invention is to disclose an acid liquid thickener, the molecular structure of the acid liquid thickener is as follows:

[0009] in: a=20000-200000; b = 4000-80000; c = 2000-40000; d=10000-200000.

[0010] Preferably, the viscosity average molecular weight of the acid liquid thickener is 10,000,000-20,000,000.

[0011] Another object of the present invention is to disclose a method for synthesizing the above acid liquid thickener, the specific steps of which are as follows: (1) Add butenediol, 4,4'-diaminostilbene-2,2'-disulfonic acid, (2-acrylamidoethyl)phosphonic acid, potassium dihydrogen phosphate and deionized water into the first reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Purge the second reactor and pipeline with nitrogen, add (3-acryloxypropyl) tris(trimethylsiloxy) silane, deionized water, hydroxypropyl methylcellulose, OP-10, and potassium dihydrogen phosphate into the reactor in sequence, stir at a high speed of 1000-1200 rpm, and adjust the pH to 7-8 with sodium hydroxide solution; (3) Add the initiator to the high-position dropping tank, drip it into the second reactor, stir at 800-1000 rpm, and when the viscosity starts to rise, quickly add the mixed liquid in the first reactor, stir at 200-300 rpm for 0.5-1 hour, then raise the temperature to 55-60°C, keep the temperature for 2-4 hours, and obtain a viscous liquid; (4) Drying and granulating the viscous liquid to obtain an acid liquid thickener.

[0012] In the present invention, preferably, based on 1 mol part of butene diol, the 4,4'-diaminostilbene-2,2'-disulfonic acid, (2-acrylamidoethyl)phosphonic acid, and (3-acryloxypropyl)tris(trimethylsiloxy)silane are 0.2-0.4 mol part, 0.1-0.2 mol part, and 0.5-1 mol part, respectively.

[0013] In the present invention, preferably, in step (1), the weight ratio of potassium dihydrogen phosphate, deionized water and butene glycol is 0.05-0.1:2-3:1.

[0014] In the present invention, preferably, in step (2), the weight ratio of deionized water, hydroxypropyl methylcellulose, OP-10, potassium dihydrogen phosphate and butylene glycol is 4-6:0.1-0.2:0.05-0.1:0.05-0.1:1.

[0015] In the present invention, preferably, in step (3), the initiator is a mixed solution of persulfate and sodium bisulfite, wherein the concentration of persulfate is 10-12wt%, the concentration of sodium bisulfite is 3-5wt%, and the weight ratio of the initiator to butene glycol is 0.3-0.5:1.

[0016] Preferably, the persulfate is one of potassium persulfate, ammonium persulfate and sodium persulfate.

[0017] The synthetic reaction equation of the acid liquid thickener of the present invention is as follows:

[0018]

[0019] The third object of the present invention is to disclose the use of the above thickener in fracturing fluid.

[0020] The acid liquid thickener of the present invention is a quaternary high molecular polymer. The polymerized monomers include butene glycol, 4,4'-diaminostilbene-2,2'-disulfonic acid, (2-acrylamidoethyl)phosphonic acid, and (3-acryloxypropyl)tri(trimethylsiloxy)silane. The molecule contains amino and hydroxyl groups, which can be cross-linked with various cross-linking agents such as boron, zirconium, and titanium to form two-dimensional and three-dimensional structures, greatly improving its viscosity; the molecule contains silane and siloxane lipophilic groups, and the molecule contains sulfonic acid hydrophilic groups, which can reduce surface interfacial tension and reduce friction resistance during the migration of fracturing fluid; the molecule contains a benzene ring structure, which can increase shear resistance; the molecule contains a phosphonic acid group, which can increase hardness resistance; hydroxypropyl methylcellulose plays the role of a dispersant in the polymerization process, which can improve the polymerization effect of the present invention, and the hydroxyl groups contained can also enhance the cross-linking effect.

[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) The acid thickener of the present invention has a relatively high apparent viscosity. When prepared into a 2000 mg / L solution with deionized water, the apparent viscosity reaches 124 mPa•s or above; (2) The acid thickener of the present invention has good shear resistance and can withstand 170s-1 Under the condition of continuous shearing for 120 minutes, the viscosity retention rate is greater than 88%; (3) The acid thickener of the present invention has good salt resistance and hardness resistance. When the concentration of 2000 mg / L is prepared with simulated formation water containing 50,000 mg / L salt and 10,000 mg / L hardness, the apparent viscosity reaches 100 mPa•s or above. (4) The acid liquid thickener of the present invention has a good drag reduction effect, and the drag reduction rate is greater than 88%. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] The technical solution of the present invention is further described below in conjunction with specific embodiments:

[0024] Example 1 (1) Add 0.2 mol of butene glycol, 0.04 mol of 4,4'-diaminostilbene-2,2'-disulfonic acid, 0.04 mol of (2-acrylamidoethyl)phosphonic acid, 0.88 g of potassium dihydrogen phosphate, and 35.2 g of deionized water into the first reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Purge the second reactor and pipeline with nitrogen, add 0.2 mol (3-acryloxypropyl) tris(trimethylsiloxy)silane, 105.6 g deionized water, 3.52 g hydroxypropyl methylcellulose, 1.76 g OP-10, and 1.76 g potassium dihydrogen phosphate into the reactor in sequence, stir at 1000 rpm, and adjust the pH to 7-8 with sodium hydroxide solution; (3) 8.8 g of initiator containing 10 wt% potassium persulfate and 3 wt% sodium bisulfite was added to the high-position dropping tank, and then added dropwise to the second reactor, and stirred at 1000 rpm. When the viscosity began to rise, the mixed liquid in the first reactor was quickly added, and stirred at 220 rpm for 1 hour. Then, the temperature was raised to 55°C, and the reaction was kept warm for 4 hours to obtain a viscous liquid. (4) Drying and granulating the viscous liquid to obtain an acid liquid thickener product.

[0025] Example 2 (1) Add 0.2 mol of butene glycol, 0.05 mol of 4,4'-diaminostilbene-2,2'-disulfonic acid, 0.038 mol of (2-acrylamidoethyl)phosphonic acid, 0.98 g of potassium dihydrogen phosphate, and 37.8 g of deionized water into the first reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Purge the second reactor and pipeline with nitrogen, add 0.18 mol (3-acryloxypropyl) tris(trimethylsiloxy)silane, 98.7 g deionized water, 3.18 g hydroxypropyl methylcellulose, 1.56 g OP-10, and 1.33 g potassium dihydrogen phosphate into the reactor in sequence, stir at 1200 rpm, and adjust the pH to 7-8 with sodium hydroxide solution; (3) 8.1 g of initiator containing 10 wt% potassium persulfate and 4 wt% sodium bisulfite was added to the high-position dropping tank and added dropwise to the second reactor. The mixture was stirred at 800 rpm. When the viscosity began to rise, the mixed liquid in the first reactor was quickly added and stirred at 230 rpm for 0.6 hours. The mixture was then heated to 58°C and kept warm for 3 hours to obtain a viscous liquid. (4) Drying and granulating the viscous liquid to obtain an acid liquid thickener product.

[0026] Example 3 (1) Add 0.2 mol of butene glycol, 0.06 mol of 4,4'-diaminostilbene-2,2'-disulfonic acid, 0.035 mol of (2-acrylamidoethyl)phosphonic acid, 1.08 g of potassium dihydrogen phosphate, and 45.2 g of deionized water into the first reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Purge the second reactor and pipeline with nitrogen, add 0.16 mol (3-acryloxypropyl) tris(trimethylsiloxy) silane, 95.6 g deionized water, 2.63 g hydroxypropyl methylcellulose, 1.48 g OP-10, and 1.46 g potassium dihydrogen phosphate into the reactor in sequence, stir at 1100 rpm, and adjust the pH to 7-8 with sodium hydroxide solution; (3) Add 7.3 g of initiator containing 11 wt% sodium persulfate and 4 wt% sodium bisulfite into the high-position dropping tank, and drip into the second reactor. Stir at 900 rpm. When the viscosity starts to rise, quickly add the mixed liquid in the first reactor. Stir at 250 rpm for 1 hour. Then raise the temperature to 60°C and keep the temperature for 2 hours to obtain a viscous liquid. (4) Drying and granulating the viscous liquid to obtain an acid liquid thickener product.

[0027] Example 4 (1) Add 0.2 mol of butene glycol, 0.07 mol of 4,4'-diaminostilbene-2,2'-disulfonic acid, 0.03 mol of (2-acrylamidoethyl)phosphonic acid, 1.43 g of potassium dihydrogen phosphate, and 49.8 g of deionized water into the first reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Purge the second reactor and pipeline with nitrogen, add 0.14 mol (3-acryloxypropyl) tris(trimethylsiloxy)silane, 88.3 g deionized water, 2.12 g hydroxypropyl methylcellulose, 1.3 g OP-10, and 1.1 g potassium dihydrogen phosphate into the reactor in sequence, stir at 1000 rpm, and adjust the pH to 7-8 with sodium hydroxide solution; (3) Add 6.6 g of initiator containing 11 wt% sodium persulfate and 5 wt% sodium bisulfite into the high-position dropping tank, and drip into the second reactor. Stir at 800 rpm. When the viscosity starts to rise, quickly add the mixed liquid in the first reactor. Stir at 300 rpm for 1 hour. Then raise the temperature to 58 °C and keep the temperature for 4 hours to obtain a viscous liquid. (4) Drying and granulating the viscous liquid to obtain an acid liquid thickener product.

[0028] Example 5 (1) Add 0.2 mol of butene glycol, 0.08 mol of 4,4'-diaminostilbene-2,2'-disulfonic acid, 0.025 mol of (2-acrylamidoethyl)phosphonic acid, 1.76 g of potassium dihydrogen phosphate, and 52.8 g of deionized water into the first reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Purge the second reactor and pipeline with nitrogen, add 0.12 mol (3-acryloxypropyl) tris(trimethylsiloxy)silane, 74 g deionized water, 1.98 g hydroxypropyl methylcellulose, 1.01 g OP-10, and 0.88 g potassium dihydrogen phosphate into the reactor in sequence, stir at 1200 rpm, and adjust the pH to 7-8 with sodium hydroxide solution; (3) Add 5.98 g of initiator containing 12 wt% ammonium persulfate and 5 wt% sodium bisulfite into the high-position dropping tank, and drip into the second reactor. Stir at 900 rpm. When the viscosity starts to rise, quickly add the mixed liquid in the first reactor. Stir at 300 rpm for 0.5 hour. Then raise the temperature to 57 °C and keep the temperature for 3.5 hours to obtain a viscous liquid. (4) Drying and granulating the viscous liquid to obtain an acid liquid thickener product.

[0029] Example 6 (1) Add 0.2 mol of butene glycol, 0.08 mol of 4,4'-diaminostilbene-2,2'-disulfonic acid, 0.02 mol of (2-acrylamidoethyl)phosphonic acid, 1.48 g of potassium dihydrogen phosphate, and 50 g of deionized water into the first reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Purge the second reactor and pipeline with nitrogen, add 0.1 mol (3-acryloxypropyl) tris(trimethylsiloxy)silane, 70.4 g deionized water, 1.76 g hydroxypropyl methylcellulose, 0.88 g OP-10, and 1.23 g potassium dihydrogen phosphate into the reactor in sequence, stir at 1100 rpm, and adjust the pH to 7-8 with sodium hydroxide solution; (3) Add 5.28g of initiator containing 12wt% ammonium persulfate and 4wt% sodium bisulfite into the high-position dropping tank, and drip into the second reactor. Stir at 800rpm. When the viscosity starts to rise, quickly add the mixed liquid in the first reactor. Stir at 200rpm for 1 hour. Then raise the temperature to 60°C and keep the temperature for 4 hours to obtain a viscous liquid. (4) Drying and granulating the viscous liquid to obtain an acid liquid thickener product.

[0030] Example 7 Test of apparent viscosity The acid thickener of the present invention is prepared into a solution with a concentration of 2000 mg / L with deionized water and heated at 60°C for 170 seconds. -1 Under the conditions of , the apparent viscosity μ0 is tested using DV-III Brookfield viscosity test.

[0031] The fracturing thickener Z-2 produced by Zhengzhou Derong Technology Co., Ltd. was used as a comparative sample. The test results are shown in Table 1.

[0032] It can be seen from Table 1 that the acid thickener of the present invention has a relatively high apparent viscosity. When prepared into a solution with a concentration of 2000 mg / L with deionized water, the apparent viscosity reaches 124 mPa•s or above, and the highest reaches 132 mPa•s. The apparent viscosity of the fracturing thickener Z-2 of Zhengzhou Derong Technology Co., Ltd. in the comparative example is 59 mPa•s, which is significantly lower than that of the present invention.

[0033] Example 8 Shear resistance test The solution of Example 7 was heated at 60°C for 170 seconds. -1 Under the conditions of continuous shearing for 120 minutes, the apparent viscosity μ1 was tested.

[0034] The shear resistance is denoted as η1, η1=μ1 / μ0× 100% The fracturing thickener Z-2 produced by Zhengzhou Derong Technology Co., Ltd. was used as a comparative sample. The test results are shown in Table 1.

[0035] It can be seen from Table 1 that the acid thickener of the present invention has good shear resistance and -1 Under the conditions of continuous shearing for 120 minutes, the viscosity retention rate is greater than 88%, and the highest is 90.8% (Example 6); while the viscosity retention rate of the fracturing thickener Z-2 of Zhengzhou Derong Technology Co., Ltd. in the comparative example is 56%, which is significantly lower than that of the present invention.

[0036] Example 9 Salt resistance and hardness resistance test Prepare simulated water: Add sodium chloride and calcium chloride to water to prepare simulated formation water with a salt content of 50,000 mg / L and a hardness of 10,000 mg / L.

[0037] The acid thickener of the present invention was prepared into a solution with a concentration of 2000 mg / L with the above-mentioned simulated water, and heated at 60°C for 170 seconds. -1 Under the conditions, the apparent viscosity μ2 is tested using DV-III Brookfield viscosity test.

[0038] The fracturing thickener Z-2 produced by Zhengzhou Derong Technology Co., Ltd. was used as a comparative sample. The test results are shown in Table 1.

[0039] It can be seen from Table 1 that the acid thickener of the present invention has good salt and hardness resistance. When the concentration is 2000 mg / L using simulated formation water containing 50,000 mg / L salt and 10,000 mg / L hardness, the apparent viscosity reaches 100 mPa•s or above, and the highest reaches 106 mPa•s (Example 5). The viscosity of the comparative example fracturing thickener Z-2 of Zhengzhou Derong Technology Co., Ltd. is 38 mPa•s, which is significantly lower than that of the present invention.

[0040] Example 10 Drag reduction rate test The solution of Example 7 was added to a borax solution (equivalent to a borax concentration of 0.05%), and the drag reduction rate η2 was tested according to the method in SY / T 6376-2008 "General Technical Requirements for Fracturing Fluids".

[0041] The fracturing thickener Z-2 produced by Zhengzhou Derong Technology Co., Ltd. was used as a comparative sample. The test results are shown in Table 1.

[0042] Table 1 Test results of apparent viscosity, shear resistance, salt resistance, hardness resistance and drag reduction rate

[0043] The acid thickener of the present invention has a good drag reduction effect, with a drag reduction rate of more than 88%, and a maximum of 90%; while the drag reduction rate of the fracturing thickener Z-2 of Zhengzhou Derong Technology Co., Ltd. in the comparative example is 77.9%, which is significantly lower than that of the present invention.

[0044] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0045] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0046] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A method for preparing an acid liquid thickener, characterized in that: The specific steps of the preparation method are as follows: (1) Add butenediol, 4,4'-diaminostilbene-2,2'-disulfonic acid, (2-acrylamidoethyl)phosphonic acid, potassium dihydrogen phosphate and deionized water into the first reactor, stir evenly, and adjust the pH to 7-8 with sodium hydroxide solution; (2) Purge the second reactor and pipeline with nitrogen, add (3-acryloxypropyl) tris(trimethylsiloxy) silane, deionized water, hydroxypropyl methylcellulose, OP-10, and potassium dihydrogen phosphate into the reactor in sequence, stir at a high speed of 1000-1200 rpm, and adjust the pH to 7-8 with sodium hydroxide solution; (3) Add the initiator to the high-position dropping tank, drip it into the second reactor, stir at 800-1000 rpm, and when the viscosity starts to rise, quickly add the mixed liquid in the first reactor, stir at 200-300 rpm for 0.5-1 hour, then raise the temperature to 55-60°C, keep the temperature for 2-4 hours, and obtain a viscous liquid; (4) drying and granulating the viscous liquid to obtain an acid liquid thickener; Based on 1 mole of butene glycol, the 4,4'-diaminostilbene-2,2'-disulfonic acid, (2-acrylamidoethyl)phosphonic acid, and (3-acryloxypropyl)tris(trimethylsiloxy)silane are 0.2-0.4 mole, 0.1-0.2 mole, and 0.5-1 mole, respectively; The molecular structure of the acid liquid thickener is as follows: , in: a=20000-200000; b=4000-80000; c=2000-40000; d=10000-200000。 2. The preparation method according to claim 1, characterized in that: In step (1), the weight ratio of potassium dihydrogen phosphate, deionized water and butene glycol is 0.05-0.1:2-3:

1.

3. The preparation method according to claim 1, characterized in that: In step (2), the weight ratio of deionized water, hydroxypropyl methylcellulose, OP-10, potassium dihydrogen phosphate and butylene glycol is 4-6:0.1-0.2:0.05-0.1:0.05-0.1:

1.

4. The preparation method according to claim 1, characterized in that: In step (3), the initiator is a mixed solution of persulfate and sodium bisulfite, wherein the concentration of persulfate is 10-12wt%, the concentration of sodium bisulfite is 3-5wt%, and the weight ratio of the initiator to butene glycol is 0.3-0.5:

1.

5. The preparation method according to claim 4, characterized in that: The persulfate is one of potassium persulfate, ammonium persulfate and sodium persulfate.

6. The acid liquid thickener prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The molecular structure of the acid liquid thickener is as follows: , in: a=20000-200000; b=4000-80000; c=2000-40000; d=10000-200000。 7. The acid liquid thickener according to claim 6, characterized in that: The viscosity average molecular weight of the acid liquid thickener is 10,000,000-20,000,000.

8. Use of the acid fluid thickener according to claim 6 or 7 in fracturing fluid.

Citation Information

Patent Citations

  • Method for preparing temperature control variable viscosity acid gelating agent by aqueous solution polymerization

    CN101864031A

  • High-temperature-resistant thickening agent for fracturing fluid, and preparation method and application thereof

    CN111019042A

  • Alkali-resistant sequestering dispersant and preparation thereof

    CN101280518A

  • High temperature resisting composite water treatment agent and preparation method thereof

    CN103466814A

  • Alkali-free viscoelastic thickening agent for polyacrylamide fracturing and preparation method of alkali-free viscoelastic thickening agent

    CN116375933A

Cited By

  • Thickening agent for high-temperature acidification and preparation method thereof

    CN120737263A

  • A thickener for high-temperature acidification and its preparation method

    CN120737263B